Formalism and the sources of international law a theory of the ascertainment of legal rules - Aspremont, Jean d'. (Oxford : Oxford University Press, 2011)
As a result of the growing prominence of international organizations and non-binding instruments there is increasing controversy as to how to delineate the boundaries of international law. This book advocates a return to a more formal way of determining what is and isn't international law.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 19, 2012).
Includes bibliographical references and index.
Keywords: International law -- Sources; International law -- Interpretation and construction